2019
DOI: 10.1074/jbc.ac118.006530
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Subdued is a moonlighting transmembrane protein 16 (TMEM16) that transports ions and phospholipids

Abstract: Transmembrane protein 16 (TMEM16) family members play numerous important physiological roles, ranging from controlling membrane excitability and secretion to mediating blood coagulation and viral infection. These diverse functions are largely due to their distinct biophysical properties. Mammalian TMEM16A and TMEM16B are Ca 2؉ -activated Cl ؊ channels (CaCCs), whereas mammalian TMEM16F, fungal afTMEM16, and nhTMEM16 are moonlighting (multifunctional) proteins with both Ca 2؉ -activated phospholipid scramblase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 40 publications
3
45
0
Order By: Relevance
“…Having shown that pH i can regulate TMEM16F ion channel activity, we next sought to examine whether pH i can also influence TMEM16F lipid scrambling activity. In order to quantify TMEM16F lipid scrambling in different pH i , we established a modified fluorescence imaging assay (Le, Le and Yang, 2019; T. Le et al ., 2019) to overcome the difficulties in precisely controlling pH i and Ca 2+ i (Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Having shown that pH i can regulate TMEM16F ion channel activity, we next sought to examine whether pH i can also influence TMEM16F lipid scrambling activity. In order to quantify TMEM16F lipid scrambling in different pH i , we established a modified fluorescence imaging assay (Le, Le and Yang, 2019; T. Le et al ., 2019) to overcome the difficulties in precisely controlling pH i and Ca 2+ i (Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…3A), TMEM16F-F518K and TMEM16F-Y563K (Fig. 3D) (Peters et al ., 2018; T. Le et al ., 2019). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With more in-depth understanding of TMEM16 CaPLSases 20 and caspase-activated lipid scramblases 27 , we now understand that a viable cell with high CaPLSase expression can effectively externalize PS to cell surface 41 without triggering apoptosis 30,42,43 . Our findings thus support that under physiological conditions, cell-cell fusion preferentially happen between healthy cells instead of involving apoptotic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the human trophoblasts exhibited robust CaPLSase activity measured by an optimized phospholipid scrambling assay (Figure S1A) 30 . We stimulated both BeWo and primary human term placental trophoblasts with ionomycin, a Ca 2+ ionophore (Figures 1F, S1B and Movies S1), or GSK-1016790A 31 , a potent and specific agonist of TRPV4 Ca 2+ -permeable channel (Figures 1G, S1D and Movie S2).…”
Section: Ps Surface Externalization Is Required For Trophoblast Fusionmentioning
confidence: 99%